2013
DOI: 10.1136/neurintsurg-2013-010800.rep
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical endovascular procedure for the treatment of acute ischemic stroke caused by total detachment of a papillary fibroelastoma

Abstract: Papillary fibroelastomas (PFEs) are rare cardiac tumors. Despite their benign nature, they are associated with a high risk of embolic complications including stroke. Endovascular treatment has been reported as a safe procedure in patients with myxoma, the most common type of primary cardiac tumor. A case of ischemic stroke due to embolization of a PFE successfully treated with a single pass of a retrievable stent is described. A 64-year-old patient with a right middle cerebral artery syndrome was treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…With the recent spread of endovascular treatment, cerebral infarction cases in which embolus removed while the patient was alive was histopathologically diagnosed as tumor embolism have been occasionally reported ( Table 1). [5][6][7][8][9][10][11][12][13][14][15] The causative tumor was benign tumor originated from the heart in many cases (10/13, 76.9%). In contrast, only three cases of tumor embolism caused by tumor not originated from the heart.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent spread of endovascular treatment, cerebral infarction cases in which embolus removed while the patient was alive was histopathologically diagnosed as tumor embolism have been occasionally reported ( Table 1). [5][6][7][8][9][10][11][12][13][14][15] The causative tumor was benign tumor originated from the heart in many cases (10/13, 76.9%). In contrast, only three cases of tumor embolism caused by tumor not originated from the heart.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, 44% of tumors were mobile (movie clips S2 and S3) and we found no relation between mobility and the presence of symptoms or embolism. It has been confirmed that material embolized to various territories may consist of fragments of the PFE or thrombotic material associated to its papillary fronds …”
Section: Discussionmentioning
confidence: 99%
“…These tumours may be an incidental finding1 or can be a rare cause of stroke,2–5 or coronary artery obstruction 6. Histologically, they are composed of a cellular fibroelastic core covered by a layer of endothelial cells, and have to be distinguished from cardiac myxomas7 and fibroelastomas,8 9 of which the latter had been reported to be presented as ischaemic stroke 10 11…”
Section: Discussionmentioning
confidence: 99%